AB0003 A mif promoter polymorphism is associated with the susceptibility to pulmonary arterial hypertension in diffuse cutaneous systemic sclerosis patients. (15th June 2017) - Lόpez-Isac, E; Bossini-Castillo, L; Campillo-Davό, D; Carmona, FD; Simeόn, CP; Carreira, P; Callejas-Rubio, JL; Castellví, I; Fernández-Nebro, A; Rodríguez-Rodríguez, L; Rivas, M Rubio; García, FJ Hernández; et al.
Abstract : Background: Systemic sclerosis (SSc) is a fibrotic immune-mediated disease of unknown etiology. Among its clinical manifestations, pulmonary involvement is the leading cause of mortality in SSc patients. However, the genetic factors involved in lung complication are not well-defined. Objectives: We aimed to revisit the association of the MIF gene, which encodes a cytokine implicated in idiopathic pulmonary hypertension among other diseases, with the susceptibility and clinical expression of SSc, besides testing the association of this polymorphism with SScrelated pulmonary involvement. Methods: A total of 4, 393SSc patients and 16, 591 unaffected controls from six cohorts of European origin were genotyped for the MIF promoter variant rs755622. An inverse variance method was used to meta-analyze the data. Results: A statistically significant increase of the MIF rs755622*C allele frequency compared to controls was observed in the subgroups of patients with diffuse cutaneous SSc (dcSSc) and with pulmonary arterial hypertension (PAH) independently (dcSSc: P=3.20E-2, OR=1.13; PAH: P=2.19E-02, OR=1.32). However, our data revealed a stronger effect size with the subset of SSc patients showing both clinical manifestations (dcSSc with PAH: P=6.91E-3, OR=2.05). Conclusions: We revisited the association of the MIF rs755622*C allele with SSc and described a phenotype-specific association of this variant with the susceptibility to develop PAH in dSSc patients. Disclosure of Interest: None declared